Comparison of Azorean tea theanine to teas from other origins by HPLC/DAD/FD. Effect of fermentation, drying temperature, drying time and shoot maturity - Baptista, José (2022)
The objectives of the present study were the determination of theanine (a specific amino acid of tea leaves with repercussion in human neuronal activity) by HPLC with o-phthaldialdehyde derivatisation prior analysis and comparison of its level in samples from different origins or from the same origin (Azores Islands) but with different processing conditions (fermentation, drying temperature and drying time) and shoot maturity. The results revealed a higher level of theanine in the Azorean green tea (3.10%), the only one produced in Europe, as compared with the Chinese, Japanese, Korean and Taiwan green teas that have an average theanine content of 1.52%, 1.34%, 0.89% and 2.76% of the dry weight (dw) of tea leaves, respectively. The fermentation for a longer period of time results in less theanine remaining (2.28% and 3.10% of dw for fermented and non-fermented tea, respectively). The drying temperature and time of the drying process have an inversely strong effect (4.45% and 5.65% of dw for dried at 55 °C during 8.50 h and at 40 °C during 7.10 h, respectively). The younger tea shoots have a higher theanine content than mature leaves (7.02% and 6.10% of dw, respectively). Our data suggested that a new type of Azorean theanine-rich tea may be produced by modifying the manufacturing processes of the younger tea shoots.